2023
DOI: 10.1097/shk.0000000000002137
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Sepsis Diagnostic Models and Identification of Macrophage Subpopulations Based on Pyroptosis-Related Genes

Abstract: Background: Numerous studies have shown that pyroptosis is associated with sepsis progression, which can lead to dysregulated host immune responses and organ dysfunction. Therefore, investigating the potential prognostic and diagnostic values of pyroptosis in patients with sepsis is essential. Methods: We conducted a study using bulk and single-cell RNA sequencing (scRNA-seq) from the Gene Expression Omnibus database to examine the role of pyroptosis in sepsis. Univariate logistic analysis, least absolute shri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Several studies have shown that these genes are closely associated with sepsis. For example, ELANE has been identified as a component of the diagnostic gene signatures in several studies [ [39] , [40] , [41] ]. In addition, ELANE serves as a target of miR-608 in human monocytes and participates in the process of inflammation; therefore, it is a novel target for the diagnosis or treatment of sepsis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that these genes are closely associated with sepsis. For example, ELANE has been identified as a component of the diagnostic gene signatures in several studies [ [39] , [40] , [41] ]. In addition, ELANE serves as a target of miR-608 in human monocytes and participates in the process of inflammation; therefore, it is a novel target for the diagnosis or treatment of sepsis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%